Application of The Icare Model to Improve Problem-Solving Ability in Momentum and Impulse Materials in Class X SMA - Utami, Alifia Mentari; Azhar; Yennita (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
The purpose of this study is to determine the problem-solving abilities of students using the ICARE model and to determine the differences in problem-solving abilities. The type of research used is experimental research with a quasi-experimental design called "nonequivalent control group design" with the "posttest only control group design" model. The population of this study is all students of class X IPA SMA Negeri 1 Tambang for the academic year 2021-2022, with a sample of 59 students consisting of class X IPA 1 as the control class, which consists of 31 students, and class X IPA 2 as the experimental class. 28 students. The data collection instrument was in the form of a test of momentum and impulse problem-solving skills for class X SMA, which consisted of 5 essay questions. The data analysis used is descriptive analysis through the results of students' problem-solving abilities and inferential analysis through normality tests, homogeneity tests, and independent-sample t-tests with the help of SPSS version 23. The results show that the results of students' problem-solving abilities in the experimental class are better than in the experimental class. control and there are differences in the results of problem-solving abilities between the experimental class that applies the ICARE model and the control class that applies the conventional learning model.